1971
DOI: 10.1159/000179916
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transport of Diatrizoate in the Rabbit, Dog, and Rat

Abstract: The renal transport of 125I-diatrizoate was examined in three species, dog, rabbit, and rat. In the rabbit this organic acid behaved like many such compounds, i.e. it was secreted by the proximal tubular organic anion process as judged by stop-flow analysis. The proximal tubular peak was abolished by probenecid. In vitro experiments with renal cortex slices gave results entirely consistent with the in vivo studies. Diatrizoate uptake by the slices was an energy-dependent, saturable process that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1974
1974
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…The effect of probenecid was investigated, because the tubular titration curve for iohexol in the IPK diverged from the theoretical curve, and a secretory component may be involved in the renal clearance of iohexol. In addition, other investigators suggested previously that the reduced renal accumulation of the contrast analogue diatrizoate, determined after pretreatment with probenecid, was a result of inhibition of organic anion transport (Mudge et al, 1971). Contrary to these findings, probenecid enhanced the clearance of iohexol in our IPK preparations.…”
Section: Discussioncontrasting
confidence: 88%
“…The effect of probenecid was investigated, because the tubular titration curve for iohexol in the IPK diverged from the theoretical curve, and a secretory component may be involved in the renal clearance of iohexol. In addition, other investigators suggested previously that the reduced renal accumulation of the contrast analogue diatrizoate, determined after pretreatment with probenecid, was a result of inhibition of organic anion transport (Mudge et al, 1971). Contrary to these findings, probenecid enhanced the clearance of iohexol in our IPK preparations.…”
Section: Discussioncontrasting
confidence: 88%
“…Although some tubular transport may occur at low doses [14,20,26,27] this becomes insignificant at doses used clinically. In the present study the upper half of our dose range covers the spectrum of clinical usage.…”
Section: Discussionmentioning
confidence: 99%
“…If tubular secretion of diatrizoate occurs in man, the proportion excreted by this route appears to be small, even at low doses [10]. In the rat, in vitro experiments with slices of renal cortex suggest that tubular secretion of diatrizoate either does not occur [29] or is small in amount [25]. Though we administered diatrizoate at a dose lower than those employed in excretion urography, we consider it unlikely that secretion by normally functioning tubules accounts for the very much greater concentrations which we found in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat too, tubular secretion either does not occur [29] or is small in amount [25], In acute renal failure the appearance of a dense nephro gram immediately after intravenous injection of diatrizoate may indicate that glomerular filtration continues [6], In man the density of this nephrogram may be as great as it is in subjects with normal renal function [5], This suggests that glomerular filtration in acute renal failure is not significantly reduced. How ever, nephrographic density is difficult to quantify [6,11,15], and much ex-perimental work in acute renal failure appears to indicate that glomerular filtration is profoundly diminished [13,26,31].…”
Section: Introductionmentioning
confidence: 99%